A new species, Didymoglossum radiatum (Hymenophyllaceae), and two new records with note to the genus Didymoglossum Desv. from Thailand - Siwakorn Chokrassameehirun; Ekaphan Kraichak; Tassanai Jaruwattanaphan (PhytoKeys)
During the filmy fern (Hymenophyllaceae) diversity study in Thailand, the genus Didymoglossum was investigated using morphological data and molecular phylogenetic analyses of the chloroplast rbcL region. This study revealed a new species, Didymoglossum radiatum S.Chokrassameehirun, Kraichak & Jaruwatt., sp. nov., which is currently known only from peninsular Thailand. This taxon resembles D. tahitense in possessing peltate fronds but differs in frond size, the structure of false veinlets, and the appearance of its sori. The phylogenetic results further confirmed the distinct phylogenetic positions of D. henzaianum and D. mindorense, which were also newly recorded and described for Thailand.